Effect of composite ingredients on vibration frequencies of plates made of functionally graded material = Wpływ składników kompozytu na częstości drgań płyt zbudowanych z materiałów o funkcyjnej gradacji własności - Wirowski, Artur (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of this paper are thin plates with characteristic material structure: periodic in selected direction and smoothly varying along another. The aim of the contribution is to formulate and apply averaged model describing the free vibrations of these plates. Modelling procedure is based on the tolerance averaging technique (TAT).
Keywords: płyty cienkie; kompozyt; technika tolerancyjnego uśredniania; drgania swobodne; materiały funkcyjnie zmienne; unctionally graded materials; thin plates; tolerance averaging technique; composite; free vibrations